Evaluation of prognostic factors and survival rates in malignant feline mammary gland neoplasms - Campos, Cecilia B. de[UNESP]; Damasceno, Karine A.; Gamba, Conrado O.; Ribeiro, Ana M.; Machado, Carla J.; Lavalle, Gleidice E.; Cassali, Geovanni D. (SAGE Publications, 2015)
To investigate the association of prognostic factors of feline mammary gland neoplasms, correlating them with overall survival (OS). Fifty-six primary malignant mammary gland neoplasms and 16 metastatic lymph nodes from 37 female cats were analyzed. Clinical staging, histologic type and grade, and immunohistochemistry for Ki-67, progesterone and estrogen receptor, human epidermal growth factor receptor type 2 (HER-2), cyclooxygenase-2 (COX-2) and vascular endothelial growth factor (VEGF) were evaluated. Follow-up was performed in order to correlate prognostic factors with OS. Lymph node metastasis was found in 35% of cases. Clinical stage III, tubulopapillary carcinomas and histologic grade II cases prevailed in the study. Most neoplasms were positive for hormonal receptors, negative for HER-2 overexpression and presented VEGF overexpression. Immunoreactivity for Ki-67 (P = 0.046) and COX-2 (P = 0.007) was higher in metastases than in primary tumors. COX-2 (P = 0.089), HER-2 (P = 0.012) and histologic grade (P = 0.080) were correlated with OS. The data suggest that inhibition of ovarian hormones and COX-2 may represent a therapeutic option for malignant feline mammary gland neoplasms. COX-2 scores and Ki-67 index should be analyzed in primary tumors and metastases, and histologic grade, HER-2 status and COX-2 scores had a direct influence in OS. Prognostic factors allow for a better understanding of disease outcome in a condition that is characterized by a poor prognosis. The present work highlights the need for further studies on endocrine therapy and COX-2 inhibitors, which could influence OS.